1991
DOI: 10.1007/bf01284070
|View full text |Cite
|
Sign up to set email alerts
|

Identification and decay of182Tl

Abstract: -A new activity with a 3s half-life at mass

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 4 publications
2
6
0
Order By: Relevance
“…Alpha decay of 184 Tl was also observed by Schrewe et al [10]. Two α lines with energies 5983 (10) and 6155 (10) keV were observed, in agreement with those reported by [8], but the authors also identified an α line originating from 184 Tl at an energy of 6066 (15) keV.…”
Section: Introductionsupporting
confidence: 86%
See 2 more Smart Citations
“…Alpha decay of 184 Tl was also observed by Schrewe et al [10]. Two α lines with energies 5983 (10) and 6155 (10) keV were observed, in agreement with those reported by [8], but the authors also identified an α line originating from 184 Tl at an energy of 6066 (15) keV.…”
Section: Introductionsupporting
confidence: 86%
“…No half-life information was deduced in this study. Bolshakov et al [14] reported on the observation of 6050 keV α particles from 182 Tl with a half-life of 2.8 (6) s. The authors of [14][15][16] deduced an upper limit of 4%, 5% and 5% respectively for the α-branching ratio of 182 Tl.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, by correlating the 46-keV ␥ ray in the focal plane with its preceding ␣ decay, it is clear that this transition is only associated with an ␣ peak with an energy of 6403͑15͒ keV. We suggest this corresponds to the previously observed ␣ decay of 182 Tl [24]. We do not have sufficient data to draw further conclusions about low-lying states in 178 Au.…”
Section: A ␣-Decay Studies Of 183 Tlmentioning
confidence: 68%
“…In the β-decay study of the same data set [47], a noticeable population of the 4 + 1 (E * = 612-keV) and 4 + 2 (E * = 1124-keV) states in the daughter 182 Hg was observed along with the previously found 6 + and 8 + feedings [45]. This also points to the presence of two long-lived states in 182 Tl: high spin (presumably, 7 + ) and low spin (presumably, I = 3-5).…”
mentioning
confidence: 95%